An Integrated Evanescent Field Sensor for the Simultaneous Measurement of Layer Refractive Index and Thickness - Matthias Jäger; Jürgen Bruns; Jessica Schneidewind; Cay Pinnow; Hassan Gargouri; Klaus Petermann (Sensors, 2021)
A novel integrated sensor for the simultaneous measurement of layer refractive index and thickness based on evanescent fields is proposed. The theoretical limits for the accuracy of the sensor were examined for the example of a <semantics>TiO2</semantics> layer. The influence of production tolerance on the accuracy was evaluated. In the experimental part of this work, a sensor chip containing nanowire and nanorib waveguides realized in silicon on insulator technology was used to demonstrate the detection of refractive index and thickness of a <semantics>TiO2</semantics> atomic layer deposition (ALD) layer.